Enterprise Resource Planning System Implementation Framework for Selected State Universities - Abejo, Maria Corazon B. (International Journal of Computing Sciences Research, 2023)
Purpose - The highly competitive education environment poses a great challenge to State Universities in the Philippines. Consequently, the need to take on new information system solutions to properly address partial and unintegrated systems is a must. This research is focused on developing an Enterprise Resource Planning (ERP) system implementation framework that would serve as a tool for improving the university’s operational efficiency. Method - In this study, the ERP critical success factors were determined through the Delphi Method, and weights were assigned to indicate their importance based on experts' consensus using Principal Component Analysis. Data collated from the selected state universities were summarized and treated to determine their readiness for the ERP system. Results - It was observed that the university with high awareness and the finest ICT practices has a strong potential in adopting the system. The organizational and socio-economic factors identified remarkably have a greater impact on the successful implementation of the system, thus, achieving this requires improvement in organizational performance and effectiveness. Generally, most of the universities in the study are ERP-ready and find the proposed framework highly acceptable as a useful reference . Conclusions - Strong executive leadership and commitment are essential elements to ensure success. It was also established that the socio-economic factors are more perceptible, therefore, enhancing employee’s knowledge of the benefits of the ERP system can increase their flexibility and involvement in ERP system projects. Recommendations - It is recommended that these universities consider using the Readiness Assessment provided in this study to assist in decision-making and the proposed framework as a guide in planning and strategizing for effective ERP implementation. Practical Implications - The framework developed may be used as a springboard for improving the university’s IT infrastructure and for upgrading their technologies leading to enhanced user experience and increased operational efficiency. This can further serve as the basis for policy intercession in the future.